Multiple types of human papillomavirus infection and anal precancerous lesions in HIV-infected men in Taiwan: a cross-sectional study. Issue 1 (27th January 2018) - Cheng, Shu-Hsing; Liao, Kuo-Sheng; Wang, Chi-Chao; Cheng, Chien-Yu; Chu, Fang-Yeh
Abstract : Objectives: This study aimed to assess the relationship between infection with multiple human papillomavirus (HPV) types and abnormal anal cytology in HIV-infected men. Design: An observational, cross-sectional study. Setting: A regional referral hospital in Taiwan. Participants: In total, 714 HIV-infected men were enrolled between March 2011 and June 2016. Thin preparation anal Pap smears were interpreted according to the 2001 Bethesda System. Thirty-seven types of HPV were detected by reverse line blotting, including 13 oncogenic types and 24 non-oncogenic types. Outcome measures: The relationship between anal HPV infection and abnormal anal cytology in people of Asian ethnicity and the coverage efficacy in HPV-vaccinated HIV-infected men. Results: On anal cytology, 175 (24.5%) subjects had atypical squamous cells of undetermined significance (ASCUS) or higher grades of dysplasia, including 87 (49.7%) with ASCUS, 73 (41.7%) with low-grade squamous intraepithelial lesions (LSILs) and 15 (8.6%) with high-grade squamous intraepithelial lesions (HSILs). A higher proportion of subjects with those without LSIL/HSIL (93.1% vs 67.3%, P<0.0001) had multiple HPV types. The odds of having LSIL/HSIL increased with an increasing number of HPV types: the ORs ranged from 1 for no HPV types to 6.96 (95% CI 2.38 to 20.37) for more than five types (Ptrend <0.0001). Multivariate logistic regression analysis showed a significant association between LSIL/HSIL and the number of HPV genotypes present (OR 1.20; 95% CI 1.02 to 1.42, P<0.05). HPV types covered by the nonavalent HPV vaccine (types 6/11/16/18/31/33/45/52/58) were detected in 70.1% of the patients in this study. Conclusions: The odds of having anal LSIL/HSIL are approximately seventimes greater in HIV-infected men with than withoutsix or more types of HPV. Multiple HPV types in HIV-infected patients deserves aggressive follow-up, and HPV vaccination programme require scaling up.